Bladder Metastasis from Clear Cell Renal Cell Carcinoma: A Case Report - İlkin Hamid-Zada; Mammad Khalilov; Özgür Efiloğlu; Asıf Yıldırım (Caucasian Medical Journal)
Kidney cancer is one of the most common urologic cancers. Generally, kidney cancer metastases occur in the liver, lungs, and bones, but we can see rare metastases such as those in the urinary bladder. Our case report describes a 60-year-old male patient with a left renal mass that was incidentally detected. After diagnosis of renal mass, left radical nephrectomy was performed. During one of these routine follow-up visits, he was admitted to our hospital with macroscopic hematuria. After transuretral resection of a suspicious lesion, the pathological results indicated metastatic carcinoma of the kidney.